(untitled) (Agroindustria, Sociedad y Ambiente, 2013)
This study is framed in the form of special project supported by field research was descriptive in nature and intended to implement Environmental Management System based on ISO 14001:2004 / Cor.1 : 2009, Clause 4.1 General Requirements , 4.2 Environmental Policy 4.3 Planning 4.4 Implementation and Operation in the production process line Short Pasta company " PASTA CAPRI " C. A. The research was conducted in three phases : the first phase is diagnosed the need for implementation of the environmental management system , for which a checklist based on the clauses of ISO 14001 dichotomous questions was developed , validated by experts and applied to the study subjects , which were a total of five (5) participants. In the second phase the environmental management system was designed in response to the steps outlined in ISO 14001:2004 / Cor.1: 2009 standard and finally the third phase corresponded to the operational and technical validation of the environmental management system, for it a tool to study subjects was applied to meet compliance with the ISO 14001:2004 should / Cor.1: 2009 standard. The environmental management system allows the company to optimize its production process, improve the use of resources, improve efficiency, minimize the environmental impact of the company with their environment due to the reduction of pollutants